The Impact of Solvency and Liquidity on Going Concern Audit Opinion - Khusmawati, Devi; A Sidik, M. Muhayin; Yuniarti, Evi (Inovasi Analisis Data, 2024)
Purpose: This research aims to examine how a company's ability to meet its financial obligations and maintain adequate cash flows influences an auditor's assessment of going concern uncertainty for manufacturers listed on the Indonesia Stock Exchange.Method: A quantitative analysis of secondary data was performed using financial information from 228 randomly selected manufacturing firms traded on the Indonesia Stock Exchange. Logistic regression was used to analyze the effect of solvency metrics and liquidity ratios on going concern audit opinions.Findings: The study uncovered that both decreasing solvency and dwindling liquidity have a statistically significant negative correlation with avoiding a going concern flag. Lower ratios for meeting debt obligations and maintaining cash were associated with a higher likelihood of an auditor expressing doubt about a company's ability to continue as a going concern.Novelty: This research provides new insights into the role of solvency and liquidity in shaping auditors' decisions within the context of manufacturing companies in Indonesia, contributing to the broader literature on financial stability and audit practices in emerging markets.Implications: The study’s findings suggest that companies should prioritize maintaining strong solvency and liquidity positions to avoid receiving going concern audit opinions. For auditors, the research underscores the need to closely monitor these financial metrics when assessing a company’s ability to sustain operations, particularly in emerging economies like Indonesia.